Value chain interventions for improving women's economic empowerment: A mixed‐methods systematic review and meta‐analysis: A systematic review - Malhotra, Suchi Kapoor; Mantri, Swati; Gupta, Neha; Bhandari, Ratika; Armah, Ralph Nii; Alhassan, Hamdiyah; Young, Sarah; White, Howard; Puskur, Ranjitha; Waddington, Hugh Sharma; Masset, Edoardo (Wiley, 2024)
Background Value chain interventions have become widespread throughout the international development sector over the last 20 years, and there is a need to evaluate their effectiveness in improving women's welfare across multiple dimensions. Agricultural value chains are influenced by socio-cultural norms and gender dynamics that have an impact on the distribution of resources, benefits, and access to opportunities. While women play a critical role in agriculture, they are generally confined to the least-valued parts of the value chain with the lowest economic returns, depending on the local, social and institutional contexts.